PENGARUH KONSENTRASI TEPUNG Spirulina platensis PADA PAKAN TERHADAP PENINGKATAN WARNA IKAN MASKOKI (Carassius auratus) Effect of Spirulina platensis Concentration in Diet to Increase Color of Goldfish (Carassius auratus) - Ricky Suranta Barus; Syammaun Usman; Nurmatias Nurmatias (AQUACOASTMARINE, 2014)
Goldfish (Carassius auratus) is a beautiful freshwater ornamental fish. Price of goldfish depends on several factors, one of them is the body color. Goldfish have stable price in the market whether market demand that continues to increase. Goldfish have characteristics from the type of colors and the beauty of their fins. Color is aesthetics ornamental fish that affect it economical values. Thus, the color should be upgraded and maintained its quality. Such efforts to increase color will be done by adding natural pigment into the feeds. Pigments natural resources can be obtained from Spirulina platensis. The purpose of this research is to know dosage Spirulina platensis that optimal to increase the color of Goldfish. This Research using Complete Random Design (CRD) with three repetition, with the dose treatment by 0 %, 1 %, 3 %, and 5 % for up during 28 days. Additional Spirulina platensis through the feed can increasing colors of the Goldfish. The nutrient that enriched with Spirulina platensis dosage 3% can produce colors brighter than the other dose. Additional Spirulina in the feed has no effect on growth of Goldfish.Keywords: Carassius auratus, Goldfish, Spirulina platensis, Color